Proceedings of the 9th International Conference on Cognitive Radio Oriented Wireless Networks 2014
DOI: 10.4108/icst.crowncom.2014.255077
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Analysis of Spectrum Occupancy in the 2.3-2.4 GHz band in Finland and Chicago

Abstract: This paper presents results from spectrum occupancy measurements in the 2.3-2.4 GHz band at Turku, Finland and Chicago, USA. The band is currently under study in European regulation and standardization for mobile communication systems. We review the recently introduced Licensed Shared Access (LSA) concept as a potential means for making the 2.3-2.4 GHz band available for mobile communications on a shared basis while protecting the rights of the incumbent spectrum users. The spectrum occupancy measurements cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The low transmission power level results in the utilization of the spectrum being deeply dependent on the location of the measurement. Hoyhtya et al [15] carried out a spectrum occupancy measurement in the 2.3-2.4 GHz band at Turku, Finland and compared this to the situation in Chicago, USA. The Finland measurement was conducted at a single point location located at Turku University of Applied Sciences Sepänkatu campus, on the roof of a four storey building.…”
Section: Related Workmentioning
confidence: 99%
“…The low transmission power level results in the utilization of the spectrum being deeply dependent on the location of the measurement. Hoyhtya et al [15] carried out a spectrum occupancy measurement in the 2.3-2.4 GHz band at Turku, Finland and compared this to the situation in Chicago, USA. The Finland measurement was conducted at a single point location located at Turku University of Applied Sciences Sepänkatu campus, on the roof of a four storey building.…”
Section: Related Workmentioning
confidence: 99%
“…The framework was introduced with the aim of offering promising opportunities for the capacity and bandwidth expansion in cellular systems [137]. The initial target bands of LSA comprise the sub-6GHz such as 2.3-2.4GHz (in Europe), and 3.5GHz (in the US) that are already owned and used by military and also Program Making and Special Events (PMSE), [2], [52], [141]. LSA licensees and incumbents provide different services, originally operate on different bands and are subject to different regulatory constraints.…”
Section: A Overview Of Lsa Frameworkmentioning
confidence: 99%
“…It is estimated that the required capacity demand, in order to accommodate such amounts of traffic load, will be remarkably increased by the growing use of mobile devices , such as smartphones to access diverse sets of broadband services and applications , as well as the development of new features like Machine Type of Communications (MTC) [1], [2], [3]. It is estimated that wide contiguous bandwidth from hundreds of MHz up to a few GHz will be required for the Roya Hosseini T ehrani, Seiamak Vahid, Dionysia T riantafyllopoulou, Haeyoung Lee, and Klaus Moessner are with the Institute for Communication Systems (ICS), University of Surrey, Guildford, GU2 7XH, U.K. E-mail:{R.HosseiniTehrani,S.Vahid, D.Triantafyllopoulou, H.Lee, K.Moessner}@surrey.ac.uk.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers, telecommunication companies and regulatory bodies have conducted studies to capture the overall spectrum utilisation within time and space. These studies have given a notable amount of insight on spectrum use as found in the literature [1,2]. Most of these studies have shown that a large amount of allocated spectrum are under-utilised resulting in a waste of valuable spectrum bandwidths, so-called spectrum holes [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%